THE EFFECT OF TOTAL SAVINGS, AMOUNT OF DEPOSITS, AND INTEREST RATE ON THE AMOUNT OF CREDIT PROVIDED BY PT. BPR MITRADANA MADANI MEDAN - Sari, Warsani Purnama; Lores, Linda; Bizlanie, Tizka (Accounting and Business Journal, 2021)
This study aims to determine the effect of the amount of savings, amount of deposits, and interest rates on the amount of credit at PT. BPR Mitradana Madani Medan, either partially or simultaneously. This type of research is an associative study. The type of data used in this research is quantitative data and the data source in this study is secondary data. The sample in this study is the total amount of savings, deposits, credit and average of interest rates per month for the period August 2014-August 2018. The techniques that researchers do to collect the data needed in the study are observation and study documentation. The data analysis technique used in this study is analysis multiple regression. The results of this study indicate that the variable amount of savings (X1) partially has a significant positive effect on the amount of credit (Y). While the variable amount of deposits (X2) has no positive and no significant effect on the amount of credit (Y). And the interest rate variable (X3) partially has a significant negative effect on the amount of credit (Y). And based on the F test, simultaneously the amount of savings, amount of deposits, and interest rates have a positive and significant effect on the amount of credit given by PT. BPR Mitradana Madani Medan.